ANALISIS PENGARUH PENERAPAN ASSET-LIABILITY MANAJEMEN (ALMA) TERHADAP RISIKO LIKUIDITAS PADA BANK PEMBANGUNAN DAERAH (BPD) SE- INDONESIA TAHUN 2012-2014 - B41111058, Niil Hendratmoko Niil (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
Abstract This study aimed to analyze the impact of assets-liability management (ALMA) application shown by ratio of LDR, NPL and CAR on the liquidity risk. The data used was obtained from financial statement published annually by each regional development bank in Indonesia from 2012 to 2014. The total samples are all regional development banks in Indonesia, 26 banks, during the period of 2012 to 2014. The analysis technique used was statistical test with multiple regression analysis and hypothesis testing was assessed with F and T test which had previously been assessed with classical assumption testing. The finding of the study showed that ALMA application shown by LDR, NPL and CAR significantly affect the liquidity risk at 5%. This showed that there is an impact of ALMA applied by regional development banks in Indonesia on liquidity risk of each bank. LDR and NPL have significant negative impact on liquidity risk while CAR has positive significant impact on liquidity risk. Based on this research, it is obtained that the R2 value is 0.387 meaning that 38.7% of dependent variable (liquidity risk) can be explained by the independent variables (LDR, NPL and CAR) while the rest with the value of 61.3% was explained by the other variables beyond the balance used by the researcher. Key words:Alma, LDR, NPL, CAR, Liquidity Risk.